2020
DOI: 10.3389/fcimb.2020.586667
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiota of the Human Mammary Ecosystem

Abstract: Human milk contains a dynamic and complex site-specific microbiome, which is not assembled in an aleatory way, formed by organized microbial consortia and networks. Presence of some genera, such as Staphylococcus, Streptococcus, Corynebacterium, Cutibacterium (formerly known as Propionibacterium), Lactobacillus, Lactococcus and Bifidobacterium, has been detected by both culture-dependent and culture-independent approaches. DNA from some gut-associated strict anaerobes has also been repeatedly found and some st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
104
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(111 citation statements)
references
References 321 publications
(466 reference statements)
2
104
3
2
Order By: Relevance
“…This is a detailed metagenomic study of the HM virome in which we first demonstrated the impact of the delivery mode, prematurity, birth weight for gestational age, and lactation period (transient or mature milk) on the composition of HM viruses. We detected viruses (bacteriophages and eukaryotic viruses) in 92.0% of all HM samples, and, as in other HM microbiome studies, the virome composition was distinguished by certain interindividual variability; each mother harbored a morphologically distinct bacteriophage population [ 8 ]. Viromes have been found in the gut, skin, respiratory tract, blood, and cerebrospinal fluid.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…This is a detailed metagenomic study of the HM virome in which we first demonstrated the impact of the delivery mode, prematurity, birth weight for gestational age, and lactation period (transient or mature milk) on the composition of HM viruses. We detected viruses (bacteriophages and eukaryotic viruses) in 92.0% of all HM samples, and, as in other HM microbiome studies, the virome composition was distinguished by certain interindividual variability; each mother harbored a morphologically distinct bacteriophage population [ 8 ]. Viromes have been found in the gut, skin, respiratory tract, blood, and cerebrospinal fluid.…”
Section: Discussionmentioning
confidence: 55%
“…Bacteriophage predominance also varies according to preterm birth, mode of delivery, and birth weight for gestational age. Both pathogenic and non-pathogenic viruses (HIV, cytomegalovirus, Ebola, and Zika) can be transmitted to infants through HM [ 8 , 9 , 17 , 28 ]. Pannaraj et al [ 16 ] analyzed the HM virome and found that bacteriophages ( Myoviridae, Siphoviridae, and Podoviridae families) made up a substantial part (95%) of the viruses present in HM, with only a few eukaryotic viruses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last 20 years, several studies have shown that human milk harbors a low biomass microbiota under physiological conditions and that milk, maternal feces, and/or infant feces share some bacteria [ 24 , 140 , 141 , 142 , 143 ]. The ultimate origin (skin, oro-nasopharynx, gastrointestinal tract, vagina) of the microbes present in human milk is difficult to elucidate because of the complex and dynamic interactions between different body locations of the mother‒infant dyad.…”
Section: The Maternal Gut‒breast Axismentioning
confidence: 99%